Health and Safety Compliance Index Optimization using Binomial Motivated Taguchi Method and Multicriteria Selection - Shedrach Aliakwe Martins; Sunday Ayoola Oke; Onoyeyan Onajite (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2021)
Previous research has examined how the safety conformity of a bottling process plant may be analysed from the lens of machine guarding usage by operators. To advance knowledge, this study pioneers how to optimize safety conformity for all operations using binomial motivated Taguchi method. Secondly, for the first time, this study analyzes the performance of segments in safety conformity of bottling plant segments using multicriteria methods. Development of binomial motivated Taguchi method includes data gathering, calculating the binomial distribution, determining levels and factors, orthogonal arrays, and the signal-to-noise ratios. Computations are made of optimal, global and specific parametric settings. The multicriteria models used entropy for weight determination and indices were obtained for 12 evaluation periods. The optimal parametric setting is obtained as A3HT-A2S-A2O-A3C1, which is -1.92E+02 for segment 1, 1.29E-01 for segment 2, -1.15E+02 for segment 3 and -1.52E+02 for segments 4 and 5. The specific optimized values (SOVs) of workers shows that SOV (segment 2) > SOV (segment 3) > SOV (segment 1) > SOV (segments 4 and 5). The best performing operations in the five segments are the rescuers (segment 1), technical operators and packer/unpacker operators (segment 2), sugar lifters (segment 3), forklift technicians (segment 4) and contractor 3 (segment 5). The binomial motivated Taguchi method is an effective tool to optimize operational activities while the multicriteria models proved effective to rank performance for optimized results. The obtained results may be useful to plan for safety budgets.